Uma proposta de metodologia do ensino de filosofia acerca do pensamento kierkegaardiano - Oliveira, Cristian Ribeiro de (2022)
To develop a critical, creative and autonomous citizen based on reflective thinking, this is the challenge that we propose in the present work, following the Kierkegaardian philosophy and seeking to dialogue with premises that encompass the existentialist philosophy and passing with considerable emphasis on the pedagogy of Paulo Freire. We chose to face the challenge of thinking about an education that aims at the construction and effectiveness of subjectivity in a process of humanization of the individual, where the edification must happen inside each existing one in the midst of its relationship with the world. We were able to achieve our goals, namely, to think about the possibility of working with Kierkegaardian thinking on the ground of the Brazilian basic education classroom, promoting constant dialogue with the contemporary educational urgency that should promote a critical awakening in the student class through existential philosophy. Within this conception, the impossibility of impartial education was proved, given that the educator must take a stand on the difficult task of being both a master and an apprentice. To think about an education that really has an effective commitment to the subjectivity of each existing, with the ethical transformation of society and the edification of people. Finally, the present work evokes the need to think about an education that has as its main objective the construction of authenticity and, consequently, the development of a critical, ethical and political conscience of people, allowing them to understand the possibility they have to change the directions of society and thus create culture.